Fores et fenestrae : a computational study of doors and windows in Roman domestic space - Michielin, Lucia, (Archaeopress Roman archaeology ;, 2021)
The role doors and windows play in shaping the life and structure of Roman private dwellings has been underestimated; they are structures that connect not only rooms but houses to the outside world, and they relate to privacy, security, and light in domestic spaces. This volume analyses these structures as an essential part of daily life.